(untitled) - Britten, Bruce (Oasis International, 2007)
Answers for Your Marriage offers practical insights to marriage issues. It also gives facts on sex, pregnancy, family planning, child-raising, money issues, adultery, HIV and sex-related diseases. Explains how to equip your children to avoid HIV. If your marriage seems hopeless, here are answers for your marriage.
Keywords: Sex -- Religious aspects